2016
DOI: 10.1080/10428194.2016.1196815
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET is prognostic and predictive for progression-free survival in relapsed follicular lymphoma: exploratory analysis of the GAUSS study

Abstract: An exploratory analysis of 75 follicular lymphoma patients treated with obinutuzumab or rituximab induction therapy (IT) for 4 weeks in the phase II GAUSS study aimed to determine whether positron emission tomography (PET) results could predict progression-free survival (PFS) and tumor response. The proportion of patients with a PFS event (progression or death) was higher in those who were PET-positive after IT (assessed using Deauville five-point scale criteria; 35/52, 67%) than PET-negative (5/20, 25%); the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…The utility of PET/CT in assessing response after end-of treatment has been confirmed in several studies 6,11,19,32. In accordance with previous findings, our study confirmed that E-PET had predictive value for PFS in FL patients, and PFS in PET-positive patients was significantly lower compared with PET-negative patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The utility of PET/CT in assessing response after end-of treatment has been confirmed in several studies 6,11,19,32. In accordance with previous findings, our study confirmed that E-PET had predictive value for PFS in FL patients, and PFS in PET-positive patients was significantly lower compared with PET-negative patients.…”
Section: Discussionsupporting
confidence: 91%
“…The interim and end-of treatment PET/CT results were assessed according to the IHP18 and D-5PS19 criteria. For IHP criteria, FDG uptake greater than the uptake of the mediastinum in lesions greater than or equal to 2 cm and more than the adjacent background tissue in lesions less than 2 cm represented residual disease.…”
Section: Methodsmentioning
confidence: 99%
“…Notwithstanding this finding, minimal residual disease analysis is showing some promise as a prognostic tool in follicular lymphoma, There is a growing body of evidence to suggest that quantitative PET measures could be prognostic in follicular lymphoma. 26,27 Analysis of baseline total metabolic tumour volume, incorporated with pretreatment prognostic indices and metabolic response, might increase separation between the progression-free survival curves of the patients with or without a complete metabolic response, specifically to better identify the 10-15% of patients with complete metabolic response who do progress early. Further PET analyses might also contribute to improved understanding of why some patients without complete metabolic response do not progress early, particularly the obinutuzumab-treated population, for whom we hypothesise that residual 18 F-FDG-avidity could reflect inflammation related to ongoing antibody-dependent cellular cytotoxicity (one of the mechanisms of action of obinutuzumab) 28,29 immediately after induction therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Applying Deauville 5-point scale evaluation with a cut-off ≤ 3, generally used for HL and DLBCL response assessment, the role of PET/CT- based outcome prediction after first-line immuno-chemotherapy for FL was reinforced 34 . Kostakoglu et al presented results of a post induction therapy in 75 patients with FL, highlighting that variations of different PET parameters were associated with PFS and response 35 . Our current data showed high diagnostic accuracy of PET/ldCT protocol in response assessment.…”
Section: Discussionmentioning
confidence: 99%